THE PENGEMBANGAN MEDIA PETA BERDERING MATERI SUKU BANGSA KELAS IV SDN KEDAWUNGKULON II PASURUAN - Nurfitrianah Putri (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The objectives of research and development of map rings are development of conventional map products to be more attractive, the implementation learning material for the ethnic the islands Indonesia, boosting student responses, and testing the effectiveness of map products from existing questionnaires filled by several sources. Method used model Dick & Carey developed that consists analysis needs and objectives, analysis of learning, analysis of students and contexts, selecting basic competencies and determining indicators, developing lesson plans, designing schemes of the front and back of the map rings, developing learning media, designing and conducting formative evaluations, revising products, and final learning media products. The results of the media expert for the map rings media showed that the media expert gave a score of 92, the material expert gave a score of 94%, and the test of the map rings media attractiveness using 5 students, obtained an average value of 94 %.